Keabsahan Putusan Mahkamah Konstitusi Nomor 90/PUU-XXI/2023 Dalam Perpesktif Realisme Hukum - Syarifah Shafira (Mahkamah : Jurnal Riset Ilmu Hukum, 2025)
The Constitutional Court (MK) Decision Number 90/PUU-XXI/2023 has attracted attention in Indonesian legal studies because it is related to the constitutionality test of the 1945 Constitution of the Republic of Indonesia (UUD 1945). The validity of this Constitutional Court Decision, when analyzed through the lens of legal realism, can be understood as the result of a compromise between the law as a norm that must be obeyed and the changing needs of society. Social factors, such as pressure from community groups or public opinion, play a significant role in influencing the Constitutional Court's decision. In this case, the Constitutional Court is tasked with interpreting the constitution in a broader context, which includes responses to socio-political dynamics and developing community aspirations. The legal realism perspective provides an understanding that the validity of the Constitutional Court Decision Number 90/PUU-XXI/2023 does not only depend on the text of the constitution, but is also influenced by developing socio-political dynamics. The Constitutional Court's decision reflects the interaction between legal norms and existing social conditions, with the Constitutional Court functioning as an institution that responds to social demands.